Effects of Ginsenoside Metabolites on GABA(A) Receptor-Mediated Ion Currents - Lee, Byung-Hwan (The Korean Society of Ginseng, 2012)
In a previous report, we demonstrated that ginsenoside Rc, one of major ginsenosides from Panax ginseng, enhances γ-aminobutyric acid (GABA) receptor(A) (GABA(A))-mediated ion channel currents. However, little is known about the effects of ginsenoside metabolites on GABA(A) receptor channel activity. The present study investigated the effects of ginsenoside metabolites on human recombinant GABA(A) receptor (α(1)β(1)γ(2s)) channel activity expressed in Xenopus oocytes using a two-electrode voltage clamp technique. M4, a metabolite of protopanaxatriol ginsenosides, more potently inhibited the GABA-induced inward peak current (I(GABA)) than protopanaxadiol (PPD), a metabolite of PPD ginsenosides. The effect of M4 and PPD on I(GABA) was both concentration-dependent and reversible. The half-inhibitory concentration (IC(50)) values of M4 and PPD were 17.1±2.2 and 23.1±8.6 μM, respectively. The inhibition of I(GABA) by M4 and PPD was voltage-independent and non-competitive. This study implies that the regulation of GABA(A) receptor channel activity by ginsenoside metabolites differs from that of ginsenosides.